RRI's Commitment to Care and Vulnerability of Agrarian Systems: The 'Problem' of Rice Straw Burning in India. (July 2020) - Pandey, Poonam
This paper employs RRI's mandate of 'commitment to care' to understand the 'problem' of rice straw burning in India and the possible ways of engaging with it. Straw burning is often framed as a linear technology or policy deficit 'problem' in need of an immediate and quick fix. Interventions and solutions emerging from such framings have so far remained ineffective. The 'commitment to care' approach enables us to situate the current practices of straw burning in a complex web of relationalities, dependencies, vulnerabilities, and affect. By doing so, the 'problem' of straw burning is rearticulated and redefined as a cumulative effect of multiple interventions, transformations, and contradictions that led to the shaping of modern agricultural systems in India. This re-articulation demands for a rethinking of engagement, remedies and responsibilities in ways that move beyond the individualization of blame and action.